A Review of János Kornai's By Force of Thought: Irregular Memoirs of an Intellectual Journey - Roland, Gérard (Journal of Economic Literature, 2008)
This article reviews the memoirs of János Kornai. The famous Hungarian economist describes his life experiences and the concurrent history of Hungary. More importantly, he leads us through his intellectual evolution, explaining how his thinking evolved, how it was influenced by events, how one research question led to another. This brings alive the intellectual and historical developments that led to Kornai's work on socialist incentives, on the theory of planning, on the economics of shortage, and on the transition from socialism to capitalism. The book takes us on a journey that encompasses large elements of the history of economic thought in the second half of the twentieth century, as well as the history of Central Europe.